POTENSI DAUN PALA (Myristica fragrans Houtt) SEBAGAI SUMBER FENOLIK - Muammar Fawwaz; Siti Nurdiansyah A; Muzakkir Baits (Faculty of Pharmacy, Universitas Muslim Indonesia, 2017)
Phenolic is a compound that having an aromatic ring with one or more hydroxyl groups. Phenolic compounds in foods can be grouped into simple phenols and folic acid. This study aimed to determine the total phenolic content of the leaf extract of nutmeg (Myristica fragrans Houtt). Leaves of nutmeg extracted using 70% ethanol, then the extract conducting qualitative analysis by reaction with FeCl3 as specific reagent. The result of this reaction is green solution, it means there are phenolic compound in the extract. The quantitative process of total phenolic was analyzed by UV-Vis spectrophotometry. A comparison used in this analysis is gallic acid; it is a standard reference in the determination of total phenolic content. Sample measured at a wavelength of 860.7 nm, which is the maximum wavelength of gallic acid. Total average content of phenolic is 183.56-mgGAE/g extract. The ethanol extract of nutmeg’s leaves have high total phenolic content, which means it is potential as antioxidant.